The post-Cold War international political development in Europe-from bipolar to unipolarity structure - Mohd. Noor Yazid (Primrose Hall Publishing Group, 2021)
This paper explores the international political development in Europe during the post-Cold War era starting from 1989. The focus of discussion is Europe in the first decade of the post-Cold War era. The end of the Cold War had a great impact on the political and institutional development in Europe. The economic weaknesses of the Soviet Union since the mid-1980s and the collapse of the Soviet Union in the 1991 strongly influenced the changes of the former communist states of Eastern Europe. The former communist states in Eastern Europe became democratic states and then became members of the North Atlantic Treaty Organization (NATO). Why did the former communist states become democratic-capitalist states after the Cold War ended? Why they join NATO? Which International Relations Theory could be applied in explaining and analysing the changes and political development in Europe? The former communist states becoming democratic-capitalist states had relationship to their political economic position during the communist regime and the achievement and position of the Soviet Union’s economic state since the mid-1980s. The role played by American is important in influencing the foreign policies of the former communist states and why they joined NATO? The structure of international politics is important in explaining the post-Cold War Europe. There was a close relationship between the international structure and the changes at the European regional level. This paper concludes that the changes of international political structure in the European continent from a bipolarity structure to a unipolarity structure strongly influenced the policies of the former Eastern European communist states. The existence of only one single strong power, a unipolarity structure, made it easier for America to control and dominate Europe. The Theory of Structural Realism (especially Offensive Realism) could be applied in explaining the international politics and institutional development in post-Cold War Europe.